Effects of Chestnut Tannin on Nutrient Digestibility, Ruminal Protease Enzymes, and Ruminal Microbial Community Composition of Sheep - Mei Sun; Peinan Liu; Yuanyuan Xing; Meimei Zhang; Yongqiang Yu; Weiyun Wang; Dabiao Li (Fermentation, 2025)
The purpose of this research was to investigate the impact of chestnut tannins (CHTs) on nutrient digestibility, nitrogen balance, in situ crude protein (CP) digestibility, protease enzymes, and microbial community composition in sheep. Eighteen 1.5-year-old sheep (43.0 ± 2.0 kg initial BW) fitted with permanent ruminal cannula were selected and randomly divided into three groups, which were fed with CHTs added at 0, 2, and 6%/kg DM. The pre-feeding period lasted for 12 days, and the actual trial period was 18 days. Rumen fluid was collected to assess in situ crude protein (CP) degradability, while rumen digesta was analyzed for total and ruminal proteolytic bacterial populations. Using one-way ANOVA in SAS to analyze data, the results indicated that 2% CHT reduced in situ degradability by 26.23%, while 6% reduced it by 58.01% in the rumen of the sheep. The CP apparent digestibility, nitrogen metabolism, and population of proteolytic bacteria of sheep were decreased in the 6% CHT group (p < 0.05), while the above indices of the 2% CHT group were not affected. Furthermore, CHT supplementation significantly altered the ruminal microbial community structure. Particularly in the 2% CHT group, the relative abundances of Bacteroidota and Prevotella increased. LEfSe analysis revealed that Bacteroidale replaced U29-B03 as the dominant microbiota at 2% CHT. Doses of 2% CHT can be incorporated into sheep diets without impairing digestion. These findings support the inclusion of CHT doses of less than 2% for enhancing protein digestion and increasing the types of beneficial bacteria in the rumen, while doses above 6% should be avoided.